Neurophysiological analysis of the clinical pull test - Tan, J; Perera, T; McGinley, J; Yohanandan, S; Brown, P; Thevathasan, W (American Physiological Society, 2018)
Postural reflexes are impaired in conditions such as Parkinson's disease, leading to difficulty walking and falls. In clinical practice, postural responses are assessed using the 'pull test', where an examiner tugs the pre-warned, standing patient backwards at the shoulders and grades the response. However, validity of the pull test is debated with issues including scaling and variability in administration and interpretation. It is unclear whether to assess the first trial or only subsequent repeated trials. The ecological relevance of a forewarned backwards challenge is also debated. We therefore developed an instrumented version of the pull test to characterize responses and clarify how the test should be performed and interpreted. In thirty-three healthy participants, 'pulls' were manually administered and pull force measured. Trunk and step responses were assessed with motion tracking. We probed for the StartReact phenomenon (where pre-prepared responses are released early by a startling stimulus) by delivering concurrent normal or 'startling' auditory stimuli. We found that the first pull triggers a different response, including a larger step size suggesting more destabilization. This is consistent with 'first trial effects', reported by platform translation studies, where movement execution appears confounded by startle reflex-like activity. Thus, first pull test trials have clinical relevance and should not be discarded as practice. Supportive of ecological relevance, responses to repeated pulls exhibited StartReact, as previously reported with a variety of other postural challenges including those delivered with unexpected timing and direction. Examiner pull force significantly affected the postural response particularly the size of stepping.